Effect of Pilates on Body Composition and Some Biochemical Parameters of Women with Type 2 Diabetes on a Low-Carbohydrate or High-Complex-Carbohydrate Diabetic Diet - BATAR, NAZLI; Ersin, Aybüke; San, Sevil; Erdem, Mustafa Genco; Demir, Halime Pulat; Güçlü, Duygu; SEVDİN, SEZEN; KERMEN, SEDA (Zamensalamati Publishing Company, 2020)
Background: The prevalence of type 2 diabetes mellitus (T2DM) has increased dramatically in the past 30 years. The World Health Organization has prepared an action plan to stop the increase in diabetes and obesity by 2025. Objectives: This study was conducted to assess the effect of pilates on body composition and some biochemical parameters in women with T2DM on a high-complex-carbohydrate diabetic diet or a low-carbohydrate/high-monounsaturated fatty acids (MUFA) diet. Methods: This experimental study was conducted on 120 woman patients with T2DM, referring to the Fatih Medical Park Hospital's Internal Medicine Department, Istanbul, Turkey, between December 2018 and June 2019. Participants were divided into 4 groups and were followed up for 12 weeks. The mean participants' age was 41.67 +/- 3.83 years. The first group received a low-carbohydrate and high MUFA (LC, MUFA) diet, the second group received a low-carbohydrate and a high-MUFA diet and did pilates (LC, MUFA + PL), the third group received a higher complex carbohydrate (HCC) diet, and the fourth group took the HCC diet and did pilates (HCC + PL). Results: According to the applied intervention method, there were significant differences between the preliminary and final measurements of bodymass index, body fat percentage, muscle mass, and fasting blood glucose, insulin, HbA1c, total cholesterol, high-density lipoprotein (HDL), low-density lipoprotein (LDL), and triglyceride (TG) values (P < 0.05). In this study, only an increase in body muscle composition of the women in the LC, MUFA + PL group was found significant (P < 0.05). The highest decrease in body fat ratio was determined again in the LC, MUFA + PL group (P < 0.05). HDLlevels of the women who did pilates increased significantly than other groups (P < 0.05). Conclusions: In the treatment of diabetes, the patient should be evaluated with a multidisciplinary team. Diet and exercise are important non-pharmacological interventions in the treatment of diabetes.
Keywords: Diabetes; Diet; Low-Carbohydrate; High-Complex-Carbohydrate; Diabetic Diet